1972
DOI: 10.1111/j.1476-5381.1972.tb07260.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Δ9‐tetrahydrocannabinol in the mouse

Abstract: Summary1. The distribution of A9-tetrahydrocannabinol-14C in the pregnant and nonpregnant mouse is very similar. High concentrations of radiolabel can be seen in the maternal liver, spleen, lungs, brown fat, adrenal glands, mammary glands, yolk sac placenta and corpora lutea. In the pregnant mouse A9-THC crosses the placenta and enters the foetuses in very low concentrations, with no apparent selective intrafoetal radiolabel accumulation sites. Autoradiograms showing the distribution of 14C-cannabinoid 2 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“…b Low free plasma concentration implies that tissue uptake will initially be limited by tissue blood fl ow; only with sustained exposure would the infl uence of lipid content of a tissue show itself fu lly (56). Studies of tissue distribution conform roughly to this pattern (50,55,57,58). In acute experiments with injection oflabeled drug, activity is very high to high in lung, liver, and kidney; high to moderate in heart, salivary gland, Harderian gland, gastric mucosa, spleen, bone marrow, pla centa, brown fat, adrenal cortex, thyroid (follicular epithelium), pituitary, mam mary gland.…”
Section: Distribution Of Ill-thc and Its Metabolitesmentioning
confidence: 79%
See 1 more Smart Citation
“…b Low free plasma concentration implies that tissue uptake will initially be limited by tissue blood fl ow; only with sustained exposure would the infl uence of lipid content of a tissue show itself fu lly (56). Studies of tissue distribution conform roughly to this pattern (50,55,57,58). In acute experiments with injection oflabeled drug, activity is very high to high in lung, liver, and kidney; high to moderate in heart, salivary gland, Harderian gland, gastric mucosa, spleen, bone marrow, pla centa, brown fat, adrenal cortex, thyroid (follicular epithelium), pituitary, mam mary gland.…”
Section: Distribution Of Ill-thc and Its Metabolitesmentioning
confidence: 79%
“…beeause these are not seen after oral administration, they are probably mierodroplets or micellar complexes of drug (55) and reflect in yet another way the hydrophobic nature of the drug, as well as providing a complication to intravenous administration. b Low free plasma concentration implies that tissue uptake will initially be limited by tissue blood fl ow; only with sustained exposure would the infl uence of lipid content of a tissue show itself fu lly (56).…”
Section: Distribution Of Ill-thc and Its Metabolitesmentioning
confidence: 96%
“…The premise that its solubility in the plasma is readily exceeded certainly is not inconsistent with the observation of its possible precipitation and localized accumulation in body organs (1). Tetrahydrocannabinol in excess of its solubility instantaneously forms a stable emulsion or micellar dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…Tetrahydrocannabinol is highly insoluble in water (1)(2)(3). This can be a critical factor in its bioavailability, pharmacokinetics, and pharmacological action.…”
mentioning
confidence: 99%
“…Previous work (McIsaac, Fritchie & others, 1971 ;Freudenthal, Martin & Wall, 1972) has shown that after intravenous administration, Al-THC is quickly distributed throughout the brain. The autoradiographs taken at varying periods after intraventricular injection showed that the A1-THC was almost completely contained within the ventricles, and that only a minute amount diffused from the intraventricular space.…”
Section: Discussionmentioning
confidence: 96%